Late-glacial and Holocene European pollen data. Issue 2 (30th November 2017) - Brewer, Simon; Giesecke, Thomas; Davis, Basil A. S.; Finsinger, Walter; Wolters, Steffen; Binney, Heather; de Beaulieu, Jacques-Louis; Fyfe, Ralph; Gil-Romera, Graciela; Kühl, Norbert; Kuneš, Petr; Leydet, Michelle; et al.
ABSTRACT: The European Pollen Database (EPD) is a community effort to archive and make available pollen sequences from across the European continent. Pollen sequences provide records that may be used to infer past vegetation and vegetation change. We present here maps based on 828 sites from the EPD giving an overview of changes in postglacial pollen assemblages in Europe over the past 15, 000 years. The maps show the distribution and abundance of 54 different pollen taxa at 500 year intervals, supported by new age-depth models and associated chronological uncertainty analysis. Results show the individualistic patterns of spread of different pollen taxa, and provide a standardized dataset for further analysis, defining a spatial context for the study of past plant and vegetation changes and other aspects of environmental history in Europe.